Clinical characteristics and serological profiles of Lyme disease in children: a 15-year retrospective cohort study in SwitzerlandResearch in context - Beat M. Greiter; Semjon Sidorov; Ester Osuna; Michelle Seiler; Christa Relly; Annette Hackenberg; Isabelle Luchsinger; Elvira Cannizzaro; Roland Martin; Martina Marchesi; Stefanie von Felten; Adrian Egli; et al. (The Lancet Regional Health. Europe)
Summary: Background: Lyme disease (LD) is caused by Borrelia burgdorferi and is the most common tickborne disease in the northern hemisphere. Although classical characteristics of LD are well-known, the diagnosis and treatment are often delayed. Laboratory diagnosis by serological testing is recommended for most LD manifestations. The objective of this study was to describe clinical characteristics and associated serological profiles in children with LD. Methods: This retrospective cohort study included children aged 0–18 years, diagnosed with LD according to current guidelines at University Children's Hospital Zurich between January 1, 2006 and December 31, 2020. Two-tier serological testing with the recomWell enzyme-linked immunosorbent assay and recomLine Western blot (MIKROGEN Diagnostik, MIKROGEN GmbH, Neuried, Germany) was performed at the Institute of Medical Microbiology, University of Zurich. Findings: In total, 469 children diagnosed with LD were included (median age, 7.9 years); 190 patients (40.5%) with Lyme neuroborreliosis (LNB), 171 (36.5%) patients with skin manifestations (erythema migrans, n = 121; multiple erythema migrans, n = 11; borrelial lymphocytoma, n = 37; and acrodermatitis chronica atrophicans, n = 2), and 108 (23.0%) patients with Lyme arthritis. We observed seasonal variations for patients with skin manifestations and LNB, with high prevalence in May–October, but not for patients with Lyme arthritis. Significant differences between LD manifestation groups were found for age, inflammatory parameters, and specificity and concentration of B. burgdorferi-specific serum antibody responses. We observed distinct patterns of pronounced serum antibody responses against B. burgdorferi antigens in LNB (IgM against VlsE, p41, and OspC) and Lyme arthritis (IgG against p100, VlsE, p58, p41, p39, and p18). Interpretation: Our study is one of the largest and most detailed for children with LD. We present unique findings regarding the differences in clinical characteristics and immune responses between various manifestations of LD in children. Funding: No specific funding to disclose for this study.